HR‐MAS MRS of the pancreas reveals reduced lipid and elevated lactate and taurine associated with early pancreatic cancer. (9th September 2014) - Wang, Alan S.; Lodi, Alessia; Rivera, Lee B.; Izquierdo‐Garcia, Jose L.; Firpo, Matthew A.; Mulvihill, Sean J.; Tempero, Margaret A.; Bergers, Gabriele; Ronen, Sabrina M.
<x xml:space="preserve">Abstract</x> The prognosis for patients with pancreatic cancer is extremely poor, as evidenced by the disease's five‐year survival rate of ~5%. New approaches are therefore urgently needed to improve detection, treatment, and monitoring of pancreatic cancer. MRS‐detectable metabolic changes provide useful biomarkers for tumor detection and response‐monitoring in other cancers. The goal of this study was to identify MRS‐detectable biomarkers of pancreatic cancer that could enhance currently available imaging approaches. We used 1H high‐resolution magic angle spinning MRS to probe metabolite levels in pancreatic tissue samples from mouse models and patients. In mice, the levels of lipids dropped significantly in pancreata with lipopolysaccharide‐induced inflammation, in pancreata with pre‐cancerous metaplasia (4 week old p48‐Cre;LSL‐KrasG12D mice), and in pancreata with pancreatic intraepithelial neoplasia, which precedes invasive pancreatic cancer (8 week old p48‐Cre LSL‐KrasG12D mice), to 26 ± 19% (p = 0.03), 19 ± 16% (p = 0.04), and 26 ± 10% (p = 0.05) of controls, respectively. Lactate and taurine remained unchanged in inflammation and in pre‐cancerous metaplasia but increased significantly in pancreatic intraepithelial neoplasia to 266 ± 61% (p = 0.0001) and 999 ± 174% (p < 0.00001) of controls, respectively. Importantly, analysis of patient biopsies was consistent with the mouse findings. Lipids dropped in pancreatitis and in invasive cancer biopsies to 29 ± 15% (p = 0.01) and 26 ± 38% (p = 0.02) of normal tissue. In addition, lactate and taurine levels remained unchanged in inflammation but rose in tumor samples to 244 ± 155% (p = 0.02) and 188 ± 67% (p = 0.02), respectively, compared with normal tissue. Based on these findings, we propose that a drop in lipid levels could serve to inform on pancreatitis and cancer‐associated inflammation, whereas elevated lactate and taurine could serve to identify the presence of pancreatic intraepithelial neoplasia and invasive tumor. Our findings may help enhance current imaging methods to improve early pancreatic cancer detection and monitoring. Copyright © 2014 John Wiley & Sons, Ltd.